Indonesian High School English Teachers’ Attitudes towards the Use of Instructional Technology during the Covid-19 Pandemic - Adaninggar Septi Subekti; Lemmuela Alvita Kurniawati (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
The present quantitative study was conducted to investigate Indonesian high school English teachers’ attitudes towards the uses of instructional technology (IT) during the Covid-19 pandemic-driven online learning. The study used a survey method of distributing an online questionnaire several months into the Covid-19 pandemic, within July 2020. 114 Indonesian high school English teachers participated in the study. It found that the teacher participants generally had positive attitudes towards the uses of IT in English online classes. They believed that IT improved teacher-student relationships, creativity, and innovation, as well as brought positive changes towards their teaching. However, more than half of them also reported that they had more failures than success stories when using IT during the pandemic. They did not believe that IT made learning more effective either. These seemingly ambivalent attitudes may be attributed to the sudden changes from the face-to-face mode of instruction to the online one during the pandemic leading to the unpreparedness of all parties involved including teachers. Based on the findings, implications and contributions are stated alongside the possible limitations and directions for future studies. Keywords: Teachers Attitude, Instructional Technology, English Teachers Attitiude